Subunit-Specific Reactivity of Autoantibodies Against Laminin-332 Reveals Direct Inflammatory Mechanisms on Keratinocytes - Bao, Lei; Li, Jing; Solimani, Farzan; Didona, Dario; Patel, Payal M.; Li, Xiaoguang; Qian, Hua; Ishii, Norito; Hashimoto, Takashi; Hertl, Michael; Amber, Kyle T. (Frontiers in Immunology, 2021)
Laminin-332 pemphigoid, is a rare and severe autoimmune blistering disease, caused by IgG autoantibodies targeting laminin-332 in the dermal-epidermal basement zone. Laminin-332 pemphigoid is characterized by variable inflammatory infiltrate and the predominance of non-complement-fixing antibodies. Given these findings, we hypothesized that IgG autoantibodies to laminin-332 directly resulted in keratinocyte expression of inflammatory factors. We performed RNA-seq on primary human keratinocytes treated with IgG from patients with laminin-332 pemphigoid. Genes for numerous cytokines and chemokines were upregulated, including CSF2, CSF3, CXCL1, CXCL5, CXCL3, CXCL8, CXCL10, CXCL1, IL6, IL7, IL15, IL23, IL32, IL37, TGFB2 as well as metalloproteases. Considering the pro-inflammatory and proteolytic effect of autoantibodies from patients with laminin-332 pemphigoid identified in our initial experiment, we next questioned whether the reactivity against specific laminin subunits dictates the inflammatory and proteolytic keratinocyte response. Then, we treated keratinocytes with IgG from a separate cohort of patients with reactivity against individual subunits of laminin-332. We identified upregulation of IL-1α, IL-6, IL-8, CXCL1, MMP9, TSLP, and GM-CSF at the protein level, most notably in keratinocytes treated with IgG from laminin β3-reactive patients. We for the first time demonstrated a pro-inflammatory response, similar to that described in keratinocytes treated with IgG autoantibodies from patients with bullous pemphigoid, providing novel insight into the pathogenesis of laminin-332 pemphigoid and laminin-332 biology.